MONITORING OF INDUSTRIAL PROCESS USING INTELLIGENT TOMOGRAPHY SYSTEM - MACMILLEN, MARC (Universiti Teknologi Petronas, 2006)
The objective of this project is to come up with a monitoring system in a pipeline or vessel of an industrial process without intrusion of the pipeline/vessel by sensor equipment. This is done by taking a set of measurements using sensors that are distributed around the periphery of the vessel/pipeline. The information obtained is then used to reconstruct the cross sectional image inside the vessel/pipeline. In an industrial process, numerous data can be collected from materials ( eg gas, liquid or solids) inside the pipeline/vessel such as flow regime, solids fraction profile, volumetric flow rate etc. Traditional monitoring systems required the sensing elements to be placed inside the vessel/pipeline thus making it intrusive. This intrusion will cause disturbance to the flow thus creating measurement errors. This project will utilize Electrical Capacitance Tomography (ECT) as its sensing method. The tomography system itself is divided into two parts namely data acquisition and data processing.